(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In modern time, Diplomacy is commonly regarded as thepolitics of international relations. It is one of the vital and valuableinstruments of foreign policy. It is important because a nation communicatesits wishes, desires, objective and goals through diplomatic relations.1